History effects and near equilibrium in adverse-pressure-gradient turbulent boundary layers - Bobke, A.; Vinuesa, Ricardo; Orlu, R.; Schlatter, Philipp (Journal of Fluid Mechanics, 2017)
Turbulent boundary layers under adverse pressure gradients are studied using well-resolved large-eddy simulations (LES) with the goal of assessing the influence of the streamwise pressure-gradient development. Near-equilibrium boundary layers were characterized through the Clauser pressure-gradient parameter β. In order to fulfil the near-equilibrium conditions, the free stream velocity was prescribed such that it followed a power-law distribution. The turbulence statistics pertaining to cases with a constant value of β (extending up to approximately 40 boundary-layer thicknesses) were compared with cases with non-constant β distributions at matched values of β and friction Reynolds number Reδ∗. An additional case at matched Reynolds number based on displacement thickness Reδ∗ was also considered. It was noticed that non-constant β cases appear to approach the conditions of equivalent constant β cases after long streamwise distances (approximately 7 boundary-layer thicknesses). The relevance of the constant β cases lies in the fact that they define a 'canonical' state of the boundary layer, uniquely characterized by β and Re. The investigations on the flat plate were extended to the flow around a wing section overlapping in terms of β and Re. Comparisons with the flat-plate cases at matched values of β and Re revealed that the different development history of the turbulent boundary layer on the wing section leads to a less pronounced wake in the mean velocity as well as a weaker second peak in the Reynolds stresses. This is due to the weaker accumulated effect of the β history. Furthermore, a scaling law suggested by Kitsios et al. (Intl J. Heat Fluid Flow, vol. 61, 2016, pp. 129-136), proposing the edge velocity and the displacement thickness as scaling parameters, was tested on two constant-pressure-gradient parameter cases. The mean velocity and Reynolds-stress profiles were found to be dependent on the downstream development. The present work is the first step towards assessing history effects in adverse-pressure-gradient turbulent boundary layers and highlights the fact that the values of the Clauser pressure-gradient parameter and the Reynolds number are not sufficient to characterize the state of the boundary layer.
CRIS-Team Scopus Importer:2023-03-21
Keywords: turbulent boundary layers; turbulent flows